VD_FINDINFO Jug / 2025 / 378 vom 28. Mai 2025 - VD Tribunal cantonal (2025)
MOTIVATION DE LA DÉCISION, PROCÉDURE ÉCRITE, EXPERTISE PSYCHIATRIQUE, DROIT D'ÊTRE ENTENDU | 20 CP, 29 al. 2 Cst., 406 al. 1 let. a CPP (CH), 409 CPP (CH)